Myeloid-driven mechanisms as barriers to antitumor CD8+ T cell activity. (February 2020) - Colligan, Sean H.; Tzetzo, Stephanie L.; Abrams, Scott I.
Highlights: CD8 + T cells are crucial for antitumor immunity. Tumors drive the production of immune suppressive MDSC and macrophages. Such MDSC and macrophages may act to impede antitumor CD8 + T cell activity. Therapies that target MDSC and macrophages boost antitumor CD8 + T cell responses. Abstract: The adaptive immune system is essential for host defense against pathogenic challenges, and a major constituent is the CD8 + cytotoxic T cell. Ordinarily, CD8 + T cells are endowed with a unique ability to specifically recognize and destroy their targets. However, in cases where disease emerges, especially in cancer, the efficacy of the CD8 + T cell response is frequently counterbalanced in a 'tug-of-war' by networks of tumor-driven mechanisms of immune suppression. As a result, antitumor CD8 + T cell activity is hampered, which contributes to clinical manifestations of disease. It is now well-recognized that prominent elements of that network include myeloid-derived suppressor cells (MDSC) and macrophages which assume tumor-supportive phenotypes. Both myeloid populations are thought to arise as consequences of chronic inflammatory cues produced during the neoplastic process. Numerous preclinical studies have now shown that inhibiting the production, trafficking and/or function of these immune suppressive myeloid populations restore antitumor CD8 + T cell responses during both immune surveillance or in response to immune-targeted interventions. Correlative studies in cancer patients support these preclinical findings and, thus, have laid the foundation for ongoing clinical trials in patients receiving novel agents that target such myeloid elements alone or in combination with immunotherapy to potentially improve cancer patient outcomes. Accordingly, this review focuses on how and why it is important to study the myeloid-T cell interplay as an innovative strategy to boost or reinvigorate the CD8 + T cell response as a critical weapon in the battle against malignancy.